Seismic behavior of asymmetric structures with different degree of irregularity - Postolov, Nikola; Volcev, Riste; Todorov, Koce; Lazarov, Ljupco (European Association of Earthquake Engineering (EAEE), 2018)
Irregularity in plan can significantly affect the desired ductile response of structures exposed to earthquake loading. Most of the seismic design codes contain provisions for control of structural irregularities. According to EN 1998-1, a building can be characterized as regular in plan, if six different conditions were satisfied, at all story levels. Some of these conditions are qualitative, but some of them that are based on the determination of eccentricity between the center of mass and the center of stiffness or torsional radius, are quantitative. In order to investigate the influence that the degree of irregularity in plan has on the behavior of the buildings on seismic loading, several mathematical models of five story RC frame structures are analyzed. The degree of irregularity is regulated with the length of the seismic wall placed at the external frame of the structure. Nonlinear dynamic analysis is performed with purpose of numerical evaluation of the seismic behavior of the structures, whereupon input ground motions from three previous earthquakes are used, Imperial Valley – El Centro 1940, Victoria Mexico – Chihuahua 1980, Chi Chi Taiwan 06 – CHY028 1999. Input acceleration histories are scaled for three different levels of seismic hazard that correspond to PGA of 0.12g, 0.24g and 0.36g. In all analyses the seismic action was applied in one direction, perpendicular to the axis of irregularity. From the obtained results it can be noticed that the maximal displacements and the interstory drifts of the structure always occur at the most distant frame from the center of stiffness. The rotations that occur at the top story of the structure are not varying significantly with respect to the irregularity degree
Keywords: EN 1998-1; Seismic behavior; Irregularity in plan; Nonlinear dynamic analysis